An Actual Natural Setting Improves Mood Better Than Its Virtual Counterpart: A Meta-Analysis of Experimental Data - Browning, Matthew H. E. M.; Shipley, Nathan; McAnirlin, Olivia; Becker, Douglas; Yu, Chia-Pin; Hartig, Terry; Dzhambov, Angel M. (Frontiers in Psychology, 2020)
Accumulating evidence indicates that simulated natural settings can engage mechanisms that promote health. Simulations offer alternatives to actual natural settings for populations unable to travel outdoors safely; however, few studies have contrasted the effects of simulations of natural settings to their actual outdoor counterparts. We compared the impacts of simulated and actual natural settings on positive and negative affect (mood) levels using a pooled sample of participants enrolled in extant experimental studies. Relevant articles were identified from a review of research published/in press by March 2020. Of 15 articles identified, five met the inclusion criteria and administered a single cross-cutting, standardized instrument (the Positive and Negative Affect Schedule; PANAS) before and after exposure. Random effects meta-analysis of pooled effects showed that positive affect increased in the actual settings but not in their simulated counterparts (Hedge's g = 0.88; 95% CI: 0.53, 1.25). We observed no difference in effects on negative affect change scores (g = -0.23; 95% CI: -0.60, 0.13), with studies generally showing reductions in negative affect in both settings. Further research with additional populations, settings, antecedent conditions and durations will provide a more robust understanding of differences in effects between these two ways to enhance mood by viewing nature.